2021
DOI: 10.1177/20499361211036592
|View full text |Cite
|
Sign up to set email alerts
|

The clinical profile, management, and outcome of febrile neutropenia in acute myeloid leukemia from resource constraint settings

Abstract: Introduction: Acute myeloid leukemia (AML) is the commonest leukemia in adults. Mortality in thew first 30-days ranges from 6% to 43%, while infections account for 30–66% of early deaths. We aim to present our experience of infections in newly-diagnosed AML. Method: This prospective, observational study, was undertaken at a tertiary care hospital in Northern India. Patients with confirmed AML (bone marrow morphology and flow cytometry) and who had developed febrile neutropenia (FN), were included. Result: A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
(70 reference statements)
1
3
0
Order By: Relevance
“…In our study, severe gram-negative neutropenic sepsis and fatal outcomes are frequently linked to stubborn gram-negative organisms such as Klebsiella, Pseudomonas, and Escherichia coli, which show resistance to various drugs. This pattern is consistent with findings from other studies, which report nearly 70% of the infections in complicated febrile neutropenia are hospital-acquired [ 9 , 17 ]. The widespread challenge posed by these multidrug-resistant gram-negative organisms in causing severe infections jeopardizes patient outcomes and increases the risk for mortality [ 2 , 11 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, severe gram-negative neutropenic sepsis and fatal outcomes are frequently linked to stubborn gram-negative organisms such as Klebsiella, Pseudomonas, and Escherichia coli, which show resistance to various drugs. This pattern is consistent with findings from other studies, which report nearly 70% of the infections in complicated febrile neutropenia are hospital-acquired [ 9 , 17 ]. The widespread challenge posed by these multidrug-resistant gram-negative organisms in causing severe infections jeopardizes patient outcomes and increases the risk for mortality [ 2 , 11 ].…”
Section: Discussionsupporting
confidence: 93%
“…Febrile neutropenia is a life-threatening oncological emergency that emphasizes the need for comprehensive research and improved therapeutic strategies to address the challenges faced by patients undergoing induction chemotherapy [ 8 , 9 ]. A developing nation such as Pakistan grapples with the complexities of the management of febrile neutropenia, where limited resources and access to advanced medical care add a layer of adversity [ 9 ]. Statistics from different developing countries report high mortality in acute leukemia, ranging between 25% to 35%, which is consistent with the results of our study [ 9 - 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FN might cause severe infection, particularly in patients receiving chemotherapy for hematologic malignancies [ 5 ]. In half of the FN episodes, the infectious pathogens remain unclear, even though adequate and routine workup for infection is applied [ 5 , 6 ]. Portugal et al originally reported the D-index as a quantitative evaluation of the severity of a patient’s neutropenia [ 7 ].…”
Section: Introductionmentioning
confidence: 99%